2010
DOI: 10.1016/j.bbamem.2010.07.024
|View full text |Cite
|
Sign up to set email alerts
|

The role of hydrophobic interactions in ankyrin–spectrin complex formation

Abstract: Spectrin and ankyrin are the key components of the erythrocyte cytoskeleton. The recently published crystal structure of the spectrin-ankyrin complex has indicated that their binding involves complementary charge interactions as well as hydrophobic interactions. However, only the former is supported by biochemical evidence. We now show that nonpolar interactions are important for high affinity complex formation, excluding the possibility that the binding is exclusively mediated by association of distinctly cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…In order to selectively monitor CTxB binding to its lipid receptor in pure Ld or Lo membrane only, we used synthetic liposomes consisting of either DOPC (Ld) or SM/Chol (Lo) and 0.1 mol% of either GM1 or bdGM1. These liposomes were then used as capture specimen in electrochemiluminescence ELISA assays to quantitatively evaluate CTxB binding (Kolondra et al, 2010; Lingwood et al, 2011). Equal GSL content in liposomes was validated by thin-layer chromatography (TLC) analysis (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…In order to selectively monitor CTxB binding to its lipid receptor in pure Ld or Lo membrane only, we used synthetic liposomes consisting of either DOPC (Ld) or SM/Chol (Lo) and 0.1 mol% of either GM1 or bdGM1. These liposomes were then used as capture specimen in electrochemiluminescence ELISA assays to quantitatively evaluate CTxB binding (Kolondra et al, 2010; Lingwood et al, 2011). Equal GSL content in liposomes was validated by thin-layer chromatography (TLC) analysis (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…The recorded data were analyzed using GraphPad Prism 5.0 software using one site-specific binding algorithm. To measure the interactions between ankBDn and its mutants with the spectrin-binding domain (ankSBD) of ankyrin a previously published protocol was used [34]. K D (equilibrium dissociation constant) and maximal binding capacity (B max ) values were calculated according to the equation B = B max * Free/(Free+K D )+nonspecific binding.…”
Section: Methodsmentioning
confidence: 99%
“…Mutational analysis of the spectrin-binding domain of erythroid ankyrin (ZU5A domain) showed that F917S substitution completely abolished the formation of the spectrin-ankyrin complex [45]. It has been suggested that this residue is crucial for the appropriate orientation of the spectrin-binding site in erythroid ankyrin.…”
Section: Relationship Between Ankyrin-binding and Lipid-binding Activmentioning
confidence: 99%
“…The major isoform of erythroid ankyrin is composed of three distinct regions: an N-terminal domain known as a membrane domain containing 24 ankyrin repeats, a central region known as a spectrin-binding domain containing three subdomains (ZU5A, ZU5B and UPA), and a C-terminal regulatory domain with its subdomain called the "death domain" (DD). Only the first of the two ZU5 domains (ZU5A) of erythroid ankyrin is directly responsible for binding β-spectrin [43,[45][46][47]. Furthermore, the ZU5A-ZU5B-UPA-DD tandem of erythroid ankyrin seems to be crucial for auto-regulation of ankyrin functions [46].…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation